Web-Based Geographic Information System Design In Madrasah In The North Area Of Tangerang District - Ika Dewi Lestari; Eva Aprianti Lutfiah Mubarok; Fx Agung Pramanto; Lucia Puspitasi; Maindarto (bit-Tech, 2022)
Many madrasah under the auspices of the Tangerang Disctrict Education Office are scattered and the public does not know where the madrasah are. So that mapping is needed to find out the distribution of these madrasah. The development of residential areas and the increasing number of residents raises several problems, including inadequate school capacity, lack of access points to schools, incomplete supporting facilities and so on. Conditions like this can disrupt the stability of education services in the northern region of Tangerang Disctrict. With the development of the world of information today makes a lot of convenience, one technology that is currently being developed is the Geographic Information System (GIS). The information system regarding school mapping is a combination of GIS and web technology, allowing the information to be visualized into the web so that it can be accessed by the wider community without any time and place limits. This system was built using the Google Maps API to display a map of the location of madrasah in the northern area of ??Tangerang district. Spatial data for madrasah was obtained from the Tangerang District Education Office. The results of the trial of the Geographic Information System application in the Northern area of ??the Tangerang Disctrict, have provided information to the community and the Education Office about mapping madrasah in the Northern Region of Tangerang Disctrict.